Transperitoneal laparoscopic heminephroureterectomy in the pediatric population: A single-centre experience using a sealing device - Aydogdu, Ibrahim; Silay, Mesrur Selcuk (Canadian Urological Association Journal, 2018)
Introduction: We sought to report the outcomes of transperitoneal laparoscopic heminephroureterectomy (LHNU) in a pediatric population and to describe the technical details of this minimally invasive surgery. Methods: Seventeen pediatric patients (18 renal units), who had consecutive transperitoneal LHNU in our department between January 2012 and July 2017 were included in the study. In all patients, diagnostic cystoscopy and retrograde pyelography were carried out immediately before the operation. A catheter was inserted in the unaffected ureter and fixed. LHNU with a transperitoneal approach was carried out in all patients with the aid of LigaSure®. After removal of the specimen, the intervention was finalized with the insertion of a drain. All intraoperative and postoperative data of the patients were recorded prospectively. Results: The average age of the patients was 55.9±35.8 months (range 8–121). The average duration of the operations was 121.7±24.0 minutes (range 100–200). The average hospitalization time was 1.6±0.4 days (range 1–2). No intraoperative complication occurred in our patients. The average followup period was 29.1±13.4 months (range 4–48). During the followup period, no complications were observed except one patient who had pyelonephritis within the first month of surgery. Conclusions: Transperitoneal LHNU is a minimally invasive method that can be used safely in pediatric patients. Using a standardized technique during the procedure is critical to increase the success and decrease the complication rates.